2007
DOI: 10.1016/j.hisfam.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Central European household and family systems, and the ‘Hajnal–Mitterauer’ line: The parish of Bujakow (18th–19th centuries)

Abstract: The article examines marriage behaviours, household patterns and household formation rules prevailing among the population of the Upper Silesian parish of Bujakow during the late 18th and the first part of the 19th century. Their character, it is argued, is crucial not only for the proper understanding of European family systems in the past, but also for accurate comparisons of family systems in Europe and Asia. The family pattern prevailing in this part of central Europe exhibited a 'hybrid' nature in many re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 53 publications
1
29
0
1
Order By: Relevance
“…In the author's previous research on several eigteenth-century communities from historical Poland, it has been shown that neither household structures, nor the patterns of leaving home and residential arrangements of the elderly in the localities under investigation fitted what scholars have usually considered typical of East-European societies (Szołtysek, 2004(Szołtysek, , 2007aSzoł-tysek & Rzemieniecki, 2005). Although these studies allowed for revealing a considerable amount of complexity in family behaviours, further insights into the actual distribution of family patterns across historical Poland required a database much more sizeable than the 5 It was P. Czap (Czap, 1983, pp.…”
Section: The Sourcesmentioning
confidence: 99%
“…In the author's previous research on several eigteenth-century communities from historical Poland, it has been shown that neither household structures, nor the patterns of leaving home and residential arrangements of the elderly in the localities under investigation fitted what scholars have usually considered typical of East-European societies (Szołtysek, 2004(Szołtysek, , 2007aSzoł-tysek & Rzemieniecki, 2005). Although these studies allowed for revealing a considerable amount of complexity in family behaviours, further insights into the actual distribution of family patterns across historical Poland required a database much more sizeable than the 5 It was P. Czap (Czap, 1983, pp.…”
Section: The Sourcesmentioning
confidence: 99%
“…3 Furthermore, scholars from central and eastern Europe are putting the 'European family system ' back on the research agenda by tracing the course of the 'Hajnal' line that supposedly divides western and eastern Europe. 4 In the Eurasian realm, the debate on the comparability and implications of stem-family forms continues. 5 Finally, there is a strong interest in the impact of late marriage and neolocal household formation on gender relations and the supposedly unique position of women in north-western European history.…”
Section: Introductionmentioning
confidence: 99%
“…6. Some recent exceptions are (Szołtysek, 2007a and (Kopczyński, 1998). Laszuk (1999, 124-125) noticed a decrease in the number of households with resident servants in those regions of Podlachia where kin coresidence was more widespread, but she did not elaborate on that issue.…”
Section: Discussionmentioning
confidence: 99%
“…The question of the incidence of servants in the eastern part of the continent suffered from both neglect and overgeneralization, which were also characteristic of studies into the Eastern European household structure and household formation rules (Szołtysek, 2007a;Sovič, 2008). First and foremost, in the older debates, the place of East-Central Europe was rather ambiguous: it was consistantly portrayed as being somewhere between the extremes of the western and eastern types (Laslett, 1983, 530;Plakans and Wetherell, 2001).…”
Section: Historiographymentioning
confidence: 99%